Patient characteristics associated with treatment choice for pelvic organ prolapse and urinary incontinence. Issue 5 (May 2016) - Sullivan, Stephanie; Davidson, Emily; Bretschneider, C.; Liberty, Abigail; Geller, Elizabeth
Abstract Introduction and hypothesis Women with pelvic organ prolapse (POP) and stress urinary incontinence (SUI) frequently undergo more than one treatment prior to settling on their final strategy. We hypothesize that women who are younger, with worse POP and SUI symptoms will desire and choose surgical treatment. Methods A retrospective cohort study was performed over 1 year identifying new patients presenting with POP and/or SUI at a university hospital. Our aim was to determine patient desire for either surgical or conservative treatment, as well as the actual treatment chosen and received after the first visit and 1 year later. To identify predictors of choice, baseline demographic characteristics were obtained. Results Of the 203 women who met the inclusion criteria, 44.3 % (90/203) desired surgery and 55.7 % (113/203) desired conservative treatment at their first visit. Women who desired surgery were more likely to be younger (p  = 0.003), sexually active (p  = 0.001), have more advanced prolapse (p  = 0.006), and have more bothersome symptoms (p  = 0.05). Of the women whodesired surgery at their first visit, 12.2 % (11/90) actually chose conservative treatment. These women were less likely to be insured (p  = 0.01). By 1 year, of the women who initially desired and subsequently chose conservative treatment, 26.5 % (30/113) had undergone surgery. The women who changed from conservative to surgical treatment were more likely to be younger (p  = 0.01), non-White (p  = 0.03), and sexually active (p  = 0.04). Conclusions In this study, younger, sexually active women were more likely to either opt for surgery initially or to change their treatment plan from conservative to surgical.